Determination of rate parameter for kinetics of nitrification - S R Juliastuti; J Baeyens; C Creemers; J Degreve (Jurnal Teknik Kimia Indonesia, 2005)
Determination of rate parameter for kinetics of nitrification The nitrification process is the bottleneck step in the total nitrogen removal. The formation of nitrate is considered as the rate limiting step in the whole process and its kinetics determine the design of the nitrification reactor. Heavy metals (Zn2+ and Cu2+) and different organic compounds are used as micropollutants. These kinetics were experimentally measured by respirometry. In line with the aim of the paper, the experimental investigation are conducted to develop design equations to describe kinetic rate relationships under optimum conditions, study the parameter influence such as pH and inhibition by reaction intermediates and inhibition by external pollutants. Results demonstrate that the maximum value of the specific growth rate of autotrophic biomass() is 1.02 day at pH=7 and decreases at pH 7.5; inhibition occurs at substrate (NH4) concentrations in excess of 15 mg N/l; inhibition occurs at increasing concentrations of NO –N and Cu2+ has more pronounced inhibitory effect than Zn2+. The inhibitory effect of organic compounds are listed as the Chlorobenzene > Trichloroethylene> Phenol> Ethyl benzene; the experimental oxygen uptake rate (OUR)-test results the autotrophic kinetic parameter values, which can be used in design equations. Keywords: Respirometry,  Autotrophic Biomass,  Nitrification, Oxygen Uptake Rate Abstrak Proses nitrifikasi merupakan langkah penting pada penurunan kadar total nitrogen. Pembentukan nitrat dianggap sebagai tahap pembatas kecepatan reaksi pada keseluruhan proses dan kinetikanya menentukan perancangan dari bagian proses nitrifikasi. Logam berat (Zn2+ dan Cu2+) dan berbagai jenis komponen organik digunakan sebagai mikropolutan. Kinetika ini secara eksperimental diukur menggunakan respirometer. Tujuan penelitian adalah mengembangkan persamaan perancangan yang menggambarkan hubungan laju kinetika pada kondisi optimum, studi pengaruh parameter seperti pH, inhibisi karena reaksi intermediat, dan inhibisi oleh polutan dari luar. Hasil penelitian ditunjukkan sebagai berikut: harga laju pertumbuhan  biomasa autotrof maksimum spesifik  adalah 1,02 hari-1 pada pH=7 dan menurun pada pH 7,5; inhibisi terjadi pada konsentrasi substrat (NH4+) lebih besar dari 15 mg N/l; inhibisi terjadi pada peningkatan  konsentrasi NO -N ;Cu2+  lebih dikenal sebagai penyebab  inhibisi  daripada Zn2+. Efek inhibisi dari komponen organik di daftar mulai dari Chlorobenzene sampai Ethylbenzen. Tes OUR menghasilkan harga parameter kinetika yang dapat dipakai pad apersamaan perencanaan  lumpur aktif nitrifikasi. Kata Kunci: Respirometer, BiomasaAutotrof, Nitrifikasi, Laju Kenaikan Oksigen